Gastroesophageal Reflux Disease in Patients with Chronic Obstructive Pulmonary Disease (Medical Forum Monthly, 2024)
Objective: To evaluate the gastroesophageal reflux symptoms in Chronic Obstructive Pulmonary Disease (COPD) patients and Upper Gastrointestinal (GI) endoscopy findings in these patients.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at Dow University Hospital & Civil Hospital Karachi from January 2013 to December 2013.Materials and Methods: 100 of COPD were selected and assessed for presence of gastro esophageal reflux (GERD) symptoms. Data was analyzed on SPSS version 13. Frequency and percentage were computed for categorical variable like gender, gastro-esophageal reflux symptoms and upper GI endoscopy finding in COPD patients with gastro esophageal reflux symptoms. Mean standard deviation was computed for quantitative variables like age, smoking (pack year), solid fuel and tea consumption (cup/day).Results: In this study of 100 patients 95 were males and 5 were female. Cough was the commonest symptom that was found in 85% patients followed by sputum production in 71% patients, retrosternal burning (68%), acid reflux (54%) and dysphagia (11%). Gastro-esophageal reflux symptoms were observed in 54 patients. Out of these 54 patients who had GER symptoms, 33(61%) patients had erosive gastro-esophageal reflux disease while 21(39%) patients non-erosive gastro esophageal reflux disease on upper GI endoscopy.Conclusion: Our study shows that higher proportion of Gastro esophageal reflux symptoms is present in COPD patients. Moreover, upper GI endoscopy can be normal in COPD patients with significant GERD symptoms.